USUL FIKIH NU: ELEMEN METODOLOGIS MAZHAB FIKIH NU - Muhammad Adib (Fakultas Syariah - IAI Al-Qolam Malang, 2019)
This paper reveals the methodological element (usul fiqh) of the “NU fiqh school”, especially those formulated and applied in Bahtsul Masail, and which qualified to be called an institution or ideology-based school of law (madhhab). Using normative, historical and philosophical approach simultaneously, this paper suggests that usul fiqh is not at all monolithic. Throughout its history, this discipline has evolved and changed in such a way, giving rise to various variants or paradigms. One of them is NU usul fiqh, an distinctive Islamic jurisprudance which is influenced by local context and logic of thinking inherited from generation to generation by NU scholars.